2016
DOI: 10.1002/jwmg.21172
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for strain‐specific immunity to pneumonia in bighorn sheep

Abstract: Transmission of pathogens commonly carried by domestic sheep and goats poses a serious threat to bighorn sheep (Ovis canadensis) populations. All‐age pneumonia die‐offs usually ensue, followed by asymptomatic carriage of Mycoplasma ovipneumoniae by some of the survivors. Lambs born into these chronically infected populations often succumb to pneumonia, but adults are usually healthy. Surprisingly, we found that introduction of a new genotype (strain) of M. ovipneumoniae into a chronically infected bighorn shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
111
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 53 publications
(119 citation statements)
references
References 35 publications
4
111
3
1
Order By: Relevance
“…Additional evidence for M. ovipneumoniae as an epidemic agent is the transmission of 1 (or occasionally 2) multi‐locus sequence types (strains) within an outbreak and a diversity of strains across outbreaks (Besser et al , Cassirer et al ). These strains of M. ovipneumoniae also link the all‐age epizootics to the recurrent lamb pneumonia epizootics that follow (Cassirer et al ). Strains detected in domestic sheep differ from those detected in domestic goats, suggesting host adaptation and coevolution within old world Caprinae (Maksimović et al ).…”
Section: Causes Of Pneumonia In Bighorn Sheepmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional evidence for M. ovipneumoniae as an epidemic agent is the transmission of 1 (or occasionally 2) multi‐locus sequence types (strains) within an outbreak and a diversity of strains across outbreaks (Besser et al , Cassirer et al ). These strains of M. ovipneumoniae also link the all‐age epizootics to the recurrent lamb pneumonia epizootics that follow (Cassirer et al ). Strains detected in domestic sheep differ from those detected in domestic goats, suggesting host adaptation and coevolution within old world Caprinae (Maksimović et al ).…”
Section: Causes Of Pneumonia In Bighorn Sheepmentioning
confidence: 99%
“…The clinical course of bighorn sheep pneumonia may appear dramatic and short, but evidence from naturally occurring and experimental infection indicates that sub‐clinical disease exists for several days to several weeks prior to development of obvious symptoms (Besser et al , Besser et al , Cassirer et al ). This delay presumably represents the time required for M. ovipneumoniae to infect the airways and disrupt the mucociliary escalator.…”
Section: Characteristics Of Respiratory Disease In Individualsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, some of our data are drawn from a year with a novel M. ovi strain introduction event (described in Cassirer et al . ), which may have resulted in particularly severe disease and marginally altered behavioral signals.…”
Section: Discussionmentioning
confidence: 99%
“…Because most reports have described this bacterium in sheep and goats, and fewer in muskoxen ( Ovibos moschatus ) ( 4 ), some have concluded that M . ovipneumoniae is specific to the subfamily Caprinae ( 5 ) or has a host range limited to Caprinae ( 6 ), despite publications describing M. ovipneumoniae in non- Caprinae species, including Beira antelope ( Dorcatragus megalotis ) with respiratory disease in Qatar ( 7 ) and in 9 cattle ( Bos taurus ) in Colorado, USA ( 8 ). Unfortunately, description of the method(s) used to identify M. ovipneumoniae in those reports was limited to stating the use of PCR with no supporting sequence data.…”
mentioning
confidence: 99%